2010
DOI: 10.1007/s11295-010-0298-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait locus (QTL) analysis of growth and vegetative propagation traits in Eucalyptus nitens full-sib families

Abstract: Tree growth and vegetative propagation are complex but important traits under selection in many tree improvement programmes. To understand the genetic control of these traits, we conducted a quantitative trait locus (QTL) study in three full-sib families of Eucalyptus nitens growing at two different sites. One family growing at Ridgley, Tasmania had 300 progeny and two clonally replicated families growing at Mt. Gambier, South Australia had 327 and 210 progeny. Tree growth was measured over several years at bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 32 publications
5
43
0
Order By: Relevance
“…Furthermore, the clustering of QTLs controlling height and basal diameter has been observed in the same mapping population of E. ulmoides (Li et al, 2014c). In most cases, no clear patterns among phenotypic correlations have been found to coincide with the co-locating QTLs (Tsarouhas et al, 2002;Gailing, 2008;Freeman et al, 2009;Thumma et al, 2010;Li et al, 2014c). In the present study, we found that 16 QTLs were unique to specific traits (Figure 2).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Furthermore, the clustering of QTLs controlling height and basal diameter has been observed in the same mapping population of E. ulmoides (Li et al, 2014c). In most cases, no clear patterns among phenotypic correlations have been found to coincide with the co-locating QTLs (Tsarouhas et al, 2002;Gailing, 2008;Freeman et al, 2009;Thumma et al, 2010;Li et al, 2014c). In the present study, we found that 16 QTLs were unique to specific traits (Figure 2).…”
Section: Discussionsupporting
confidence: 72%
“…Previous QTL studies on main crops have frequently detected regions of the genome that contain clusters of QTLs for highly correlative traits (Zeng et al, 2009;Avia et al, 2013;Bian et al, 2013). Clusters of QTLs were also observed for growth traits and various leaf traits in poplar (Bradshaw and Stettler, 1995;Wu et al, 1997), for wood properties and growth traits in the genus Eucalyptus (Verhaegen et al, 1997;Freeman et al, 2009;Thumma et al, 2010), for growth traits in Salix (Tsarouhas et al, 2002;Ronnberg-Wastljung et al, 2005), for leaf morphological characters in European beech (Scalfi et al, 2004) and oak (Gailing, 2008;Gailing et al, 2013), and for chemical compositions in peach (Eduardo et al, 2013) and oil palm (Montoya et al, 2013). Furthermore, the clustering of QTLs controlling height and basal diameter has been observed in the same mapping population of E. ulmoides (Li et al, 2014c).…”
Section: Discussionmentioning
confidence: 99%
“…This approach was possible due to the existence of reference genome sequence available or when common markers exist between the different linkage maps [46]. Figure 4 shows the BLASTN results, in which essentially all the LGs were found to have full synteny with the reference genome used, except for markers that were unassigned to a chromosome (chromosome Un - Chr unassigned) or those that were not present in the genome of Citrus sinensis (Chr N).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Much research on eucalypt somatic embryogenesis has focused on species, particularly E. globulus and its related species, E. dunnii and E. nitens, that are difficult to propagate from cuttings [14,27,29,[32][33][34].…”
Section: Somatic Embryogenesismentioning
confidence: 99%